Supporting Those Who Provide Support: Work-Related Resources and Secondary Traumatic Stress Among Victim Advocates - Benuto, Lorraine T. (Saf Health Work, 2019)
BACKGROUND/AIMS: Victim advocates are at risk of developing secondary traumatic stress (STS), which can result from witnessing or listening to accounts of traumatic events. This study investigated the relationship between victim status, years of experience, hours of direct contact with victims, and availability of workplace supports in the development of STS. RESULTS: Of the 142 victim advocates, 134 were women. Regression analyses revealed that the only significant predictor of STS was the number of direct hours of victim services provided. CONCLUSION: The findings from this study found that women have high rates of STS and that more workplace support needs to be implemented.